2021
DOI: 10.3390/ani11030778
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width Has a Negative Prognostic Role in Dogs with Myxomatous Mitral Valve Disease

Abstract: Red cell distribution width (RDW) is a quantitative measurement of anisocytosis. This hematological parameter is an important prognostic biomarker for different cardiovascular disorders in humans but its influence on survival has been poorly investigated in dogs with cardiovascular disease. The RDW and various clinical, complete blood count, serum biochemical and echocardiographic variables were retrospectively investigated in 146 client-owned dogs with myxomatous mitral valve disease (MMVD) at various disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
(87 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, no correlation was found between RDW and RDW/Ca, and RBC, Hb and Hct, with the only exception of weak negative correlation between RDW and Hct. The association between RDW and regenerative anemia has been demonstrated in previous studies on dogs with various systemic and cardiovascular disorders [22][23][24][25][26][27][28][29]. Our findings suggest that the increased RDW and RDW/Ca in non-survivor dogs were not correlated to anemia and confirmed that anemia was not associated with a negative prognosis in dogs with AP [1][2][3]7].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, no correlation was found between RDW and RDW/Ca, and RBC, Hb and Hct, with the only exception of weak negative correlation between RDW and Hct. The association between RDW and regenerative anemia has been demonstrated in previous studies on dogs with various systemic and cardiovascular disorders [22][23][24][25][26][27][28][29]. Our findings suggest that the increased RDW and RDW/Ca in non-survivor dogs were not correlated to anemia and confirmed that anemia was not associated with a negative prognosis in dogs with AP [1][2][3]7].…”
Section: Discussionsupporting
confidence: 83%
“…The reference ranges of hematological variables, including RDW, can vary for different laboratories and the harmonization of red cell sizing is an issue in both human and veterinary hematology [ 35 , 45 ]. Indeed, despite the RDW cut-off of 12.7% identified in the present study falls within the reference intervals of the used instruments, the results suggest that some individuals with increased RDW values, even if within the reference intervals, may have a negative outcome, as already observed in dogs with myxomatous mitral valve disease [ 25 ].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Similar to the developments in human medicine, some studies investigating the use of RDW as a novel marker have also been recently published in various animal clinical settings. In particular, these studies have been conducted in small animals with cardiovascular disease [ 10 , 11 , 12 , 13 , 14 , 15 ] and other various disorders [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, the aim of this review is to provide the most relevant information on RDW evaluation in the dog.…”
Section: Introductionmentioning
confidence: 99%